2019
DOI: 10.3389/fvets.2019.00404
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Drowning and the Value of the Diatom Test in Veterinary Forensic Pathology

Abstract: The detection of diatoms into the organs is considered an important “biological marker” for the diagnosis of drowning in human pathology, but it still has a high possibility for false positive results. The aims of this study were: (1) to evaluate the contribution of pathological examination in drowning cases and (2) to investigate the differences in the number and location of diatoms between animals who died in drowning and non-drowning conditions. For these purposes, 30 dead adult dogs were selected for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 33 publications
0
13
1
Order By: Relevance
“…48 A study on drowned and nondrowned dogs concluded that pulmonary congestion, edema, and hemorrhages in the lung were present in both groups and therefore was deemed an unreliable indicator of drowning. 50 In addition, changes in reticulum fiber structures in lung tissues as a histological criteria for death by drowning 28,53 could not be confirmed in later investigations, 15 nor in this study. Hyphema in cetaceans was significantly related to drowning by others 1,13 and was observed in 5 of the 11 confirmed bycatch cases.…”
Section: Findings Related To the Drowning Processcontrasting
confidence: 57%
See 1 more Smart Citation
“…48 A study on drowned and nondrowned dogs concluded that pulmonary congestion, edema, and hemorrhages in the lung were present in both groups and therefore was deemed an unreliable indicator of drowning. 50 In addition, changes in reticulum fiber structures in lung tissues as a histological criteria for death by drowning 28,53 could not be confirmed in later investigations, 15 nor in this study. Hyphema in cetaceans was significantly related to drowning by others 1,13 and was observed in 5 of the 11 confirmed bycatch cases.…”
Section: Findings Related To the Drowning Processcontrasting
confidence: 57%
“… 38 In our study, no sign of foreign material was observed in histological sections of lung, although no further attempt was made to specifically assess the presence of diatoms. This method has proven to be informative on the diagnosis of drowning in dogs 50 and terrestrial wildlife, 10 but less useful in animals that live in the marine environment and have fish in their diet, like otters, 10 cetaceans, and sea turtles. 55 Its applicability for marine species therefore requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of a fox, a coypu and a mink, the samples of the drowning medium confirmed the presence of the same populations of diatoms found in the organs examined. As demonstrated by Piegari et al the number and presence of diatoms in certain districts, such as the sternal medulla, can be considered as a valid tool in the definition of death by drowning ( 26 ). To confirm the diagnosis, the diatom test was applied to target tissues of a coypu and a mink, dead from causes other than drowning, with negative results (absence of diatoms).…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of animal drowning is unknown, and the literature addressing this topic is sparse [ 40 , 41 ]. A drowning diagnosis in animals is even more complex than in humans due to the different anatomophysiological respiratory system specificities of the species, and it remains a challenge both for human and veterinary forensics [ 42 ]. There are no pathognomonic drowning necropsy findings; therefore, drowning remains an exclusion diagnosis based on the circumstances of death and nonspecific findings of the necropsy [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are no pathognomonic drowning necropsy findings; therefore, drowning remains an exclusion diagnosis based on the circumstances of death and nonspecific findings of the necropsy [ 43 ]. As in humans, in suspected cases, the presence of diatoms can be investigated [ 42 ], although this was not found necessary in the only case present in this study.…”
Section: Discussionmentioning
confidence: 99%